Vein matching using line pattern - Wong, Adrian Kah Hui (2014)
The number of people using mobile phones has been growing exponentially since their introduction, and this figure is expected to grow in the many years to come. Such devices are becoming increasingly indispensable to human and are also getting increasingly powerful as time goes by. Mobile phone has grown into a powerful digital device, a smartphone, which can provide many services to the user, including some which handles highly confidential information. These information calls for a demand in protection services and authentication purposes.